MENGELOLA SUMBER DAYA MANUSIA DALAM MENYONGSONG MILLENIUM DEVELOPMENT GOALS (MDGS) - Sri Budhi, Made Kembar (INPUT Jurnal Ekonomi dan Sosial, 2012)
Human Resource is one of the production factors which should be managed in proper way to create a maximum performance of the organization. At least in the era of Millennium Development Goals (MDGs), the management planning of human resource including how to empowering, improving the competence and quality, should be steered into the achievement of opportunity searching ability which possibly affecting the development acceleration that also become important necessity. The real condition of employment which activate the speed of organization could be categorized in 3 groups, ? rst, “a supper keeper” human resource is the group of employee who produce the excellent working above the average and at the same time inspire the other employees to create the same thing for the organization; second, “a keeper” human resource is the group of employee who are only able to ful? ll exactly like the organization want; and third, a mis? t human resource is the group of employee who are performing lower performance than the organization target. The right management model for all groups will be able to bring the sustainability in operational process of organization. One of the best way is investment allocation policy that focusing on the ? rst category. This will give the positive impact to employee to bring the excellent working atmosphere to the organization. Moreover, the reward policy that appropriate to each performance of the employee also the right solution, surely through the forum that is agreed by all parties in organization.
Keywords: Human resource, organization, MDGs